Innovative Approaches to Postpartum Urogenital Health: A Pilot Study on the Therapeutic Effects of Topical Oxygen and Hyaluronic Acid - Garoia, Flavio; Bertozzi, Elena; Mori, Silvia; Condemi, Leone (Open Access Macedonian Journal of Medical Sciences, 2025)
BACKGROUND: The postpartum period challenges women with a variety of urogenital disorders, which significantly impact their physical and psychological well-being. Traditional treatments often fall short in addressing the complexities of these conditions, which include urinary incontinence and sexual dysfunction. AIM: This study explores the effectiveness of a novel treatment—high-concentration oxygen combined with hyaluronic acid—aimed at improving postpartum urogenital health. METHODS: This clinical study enrolled 41 postpartum women aged 18 to 42, undergoing a four-week treatment regimen with high-concentration oxygen combined with hyaluronic acid. This device delivers high-concentration oxygen and hyaluronic acid directly to the vaginal area. The severity of symptoms such as vulvar laxity, urogenital triangle lowering, and urethral orifice laxity was assessed at baseline and post-treatment using a four-point scale. RESULTS: Treatment resulted in significant improvements in all targeted symptoms, with the most notable reductions observed in muco-epithelial inflammation scar (60% reduction) and vulvar laxity (54% reduction). These improvements were statistically significant (p<0.0001), indicating a robust response to the therapy. The study also noted enhancements in general well-being, although these were not statistically significant. CONCLUSIONS: The treatment with high-concentration oxygen and hyaluronic acid offers a promising new approach to postpartum rehabilitation. By significantly reducing key symptoms of urogenital dysfunction, this treatment has the potential to enhance the quality of life for postpartum women. Future studies should investigate long-term outcomes and the integration of this therapy into broader postpartum care practices.